PERTANIAN PADI, DILEMA PEMBANGUNAN DAERAH DI KABUPATEN KUBU RAYA - Rinaldi, Hasymi; Agus Eko Tedjo Sasongko; Mahendra Jaya (JURUSAN ADMINISTRASI BISNIS POLITEKNIK NEGERI PONTIANAK, 2024)
There has been a consistent decline in rice production in Kubu Raya since 2021, despite previously being a prominent player in provincial-level rice production. This research aims to identify the reasons for the decrease in rice farming productivity and how the local government is responding to this situation. The method used is a mixed-method approach. Quantitative analysis employs Location Quotient, Dynamic Location Quotient, and Shift Share to identify leading sectors, sectors with potential for growth, and regional economic shifts. Since these analytical tools are unable to explain the decline in rice farming productivity, a qualitative approach was also employed, including interviews, focus group discussions (FGD), and document studies. The results indicate that the agriculture, forestry, and fisheries sector is not a leading sector, nor a potential one to be promoted in Kubu Raya Regency. Several factors contributing to the stagnation in rice growth are (1) the extensive peatland, (2) land conversion, (3) climate change, (4) low farmer income, and (5) a limited number of productive farmers. Nevertheless, the local government continues to make maximum efforts to promote agricultural growth in Kubu Raya Regency, despite several policies failing to stimulate rice farming growth.